Faktor-Faktor yang Mempengaruhi Kepatuhan Pengobatan Penderita TB Paru Di Puskesmas Wonoayu Kabupaten Sidoarjo - Indah Tripuji Lestari; Valiandri puspadina; Bigun Nafilatul Izza (AFAMEDIS, 2021)
Pulmonary tuberculosis is an infectious disease that is still the world’s attention. The Wonoayu Health Center in 2016 was included in the top 10 cases of TB in Puskesmas in Sidoarjo Regency with a total of a 47 cases of pulmonary tuberculosis patients. This research was conducted to determine the factors that influence the treatment compliance of patients with pulmonary tuberculosis. Type of analytic survey research with cross sectional design. The population was all pulmonary tuberculosis patients at Wonoayu Health Center from March 11, 2019 – May 11, 2019 totaling 77 people, a sample of 65 people was taken using a purposive sampling technique with inclusion and exclusion criteria. The independent variables are education, knowledge, officer attitudes, patient attitudes, family support, and distance of the house. The dependent variable is medication adherence. Statistical analysis using the chi square test with a confidence level of 95% or α = 0,05. Statistical result showed all variables had a relationship with medication adherence, namely knowledge (p = 0,002), patient attitudes (p = 0,002), attitudes of officers (p = 0,000), family support (p = 0,002), distance (p = 0,000), education (p = 0,000). The conclusion of this study is that the factors that influence adherence to treatment of pulmonary TB patients are knowledge, patient attitudes, officer attitudes, family support, distance, and education with a value (p < 0,05).